Tourism mobility and climate change - A review of the situation in Austria. (June 2021) - Gühnemann, Astrid; Kurzweil, Agnes; Mailer, Markus
Abstract: This paper reviews and assesses the current state of knowledge on the complex relationship between tourism travel and climate change for the case study of Austria, taking into account developments to date and expected future trends of tourism-related transport and their impacts on greenhouse gas emissions as well as impacts of climate change on tourist travel. Three quarters of tourists travel to and from Austria by car and approximately 10% by plane, contributing significantly to the sector's GHG emissions. Should pre-COVID 19 trends continue, an expansion of further distant home markets and an increase of guests arriving by plane can be expected. Low-carbon technologies, intelligent mobility management and societal trends towards shared mobility solutions can improve the environmental performance of tourist travel but will not suffice to achieve the Paris Agreement's climate targets. Further strong incentives will be necessary to avoid these unsustainable forms of mobility and shift trips to climate-friendly modes of transport and the number and distance of tourism trips can be reduced by focussing marketing on closer rather than long-distance home markets and promotion of longer stays. Local tourism stakeholders in Austria can contribute by awareness-raising campaigns and promoting sustainable mobility solutions at the destinations. Politics need enable this shift by setting framework conditions such as full incorporation of climate costs for all modes of travel. Management implications: To reduce travel related GHG emissions significantly, tourism cannot only rely on technological solutions (electric vehicles) and trends (sharing) but must also initiate a shift from air and private road transport to rail and public transport. This requires measures that offer incentives (fast and direct train and bus connections, climate-friendly local transport, luggage services, attractive all-in packages, etc.), but also a focus on closer rather than long-distance home markets, promotion of longer stays and awareness-raising campaigns for local stakeholders and tourists. The awareness created by the COVID-19 and climate crises can be seen as an opportunity to take these measures. Highlights: Tourist travel in Austria contributes significantly to the sector's GHG emissions. Carbon-intensive travel modes, particularly car and long-distance flights, dominate. Technological solutions and societal trends can only partially solve the problem. Strong incentives are needed to shift to climate-friendly modes of travel. The sector should promote closer source markets and longer stays to reduce travel.